Axial length to corneal radius of curvature ratio and refractive error in Chinese preschoolers aged 4–6 years: a retrospective cross-sectional study - Yan Li; Kai Wang; Tao Tang; Heng Zhao; Mingwei Zhao; Duanke Liu; Xuewei Li (BMJ Open)
Objective This study aims to investigate the associations of axial length to corneal radius of curvature (AL/CRC) ratio with refractive error and to determine the effect of AL/CRC ratio on hyperopia reserve and myopia assessment among Chinese preschoolers.Methods This was a retrospective cross-sectional study that evaluated subjects aged 4–6 years. AL and CRC were obtained using a non-contact ocular biometer. Correlation analysis was performed to explore the associations of AL/CRC ratio with spherical equivalent refractive error (SER). The accuracy of AL/CRC ratio for hyperopia reserve and myopia assessment was analysed using cycloplegic refraction by drawing receiver operating characteristic (ROC) curves.Results The analysis included 1024 participants (537 boys, 52.4%). The mean AL/CRC ratios in hyperopes, emmetropes and myopes were 2.90±0.06, 2.95±0.05 and 3.08±0.07, respectively. The SER was found to be more strongly correlated with AL/CRC ratio (ρ=−0.66, p<0.001) than either AL or CRC alone (ρ=−0.52, p<0.001; ρ=−0.03, p=0.33, respectively). AL/CRC was correlated with SER in hyperopes (ρ=−0.54, p<0.001), emmetropes (ρ=−0.33, p<0.001) and myopes (r=−0.67, p<0.001). For low hyperopia reserve assessment, the area under the ROC curves of AL/CRC ratio was 0.861 (95% CI 0.829 to 0.892), the optimal cut-off value of the AL/CRC ratio was ≥2.955. For myopia assessment, the area under the ROC curves of AL/CRC ratio was 0.954 (95% CI 0.925 to 0.982), the optimal cut-off value of the AL/CRC ratio was ≥2.975.Conclusions The SER showed a better correlation with AL/CRC ratio than either AL or CRC alone, especially in myopes, among children aged 4–6 years. These findings indicate that when cycloplegic refraction is unavailable, AL/CRC ratio could be used as an alternative indicator for identifying low hyperopia reserve and myopia among preschoolers, helping clinicians and parents screen children with low hyperopia reserve before primary school in a timely manner.